Effect of bilateral uterine artery ligation on blood loss during total laparoscopic hysterectomy - El-Minawi, Ahmed; El-shenoufy, Hossam; Hussein, Ahmed; El-fazary, Hesham; Bahaa, Mostafa M.; Alsharif, Alaa A.; AlRasheed, Hayam Ali; Eldardiry, Mostafa (Frontiers in Medicine, 2025)
BackgroundHysterectomy is a common major gynecological surgery. Total laparoscopic hysterectomy (TLH) has become a preferred method over traditional approaches due to its minimally invasive nature and reduced postoperative complications.AimThis study aimed to compare conventional total laparoscopic hysterectomy (CTLH) with TLH involving bilateral uterine artery ligation (BUAL) at its origin, specifically evaluating blood loss and perioperative outcomes.MethodsIn this prospective randomized study conducted at Cairo University Hospital, 60 female patients undergoing TLH for benign uterine conditions were randomized. Group 1 (BUAL) involved bilateral uterine artery ligation at its origin, and Group 2 (CTLH) followed conventional TLH techniques. Preoperative assessments included comprehensive history, physical examinations, and relevant laboratory tests. Outcomes measured were intraoperative blood loss, operative time (from insufflation to skin suturing), intraoperative and postoperative complications, postoperative analgesic needs, and hospital stay.ResultsBoth groups were demographically similar. The BUAL group experienced significantly lower blood loss (103.7 ± 23.27 mL) compared to the CTLH group (128.7 ± 42.57 mL) (p < 0.05). However, the mean operative time was slightly longer in the BUAL group (169.33 ± 15.85 min) than in the CTLH group (160.50 ± 19.75 min). No major surgical complications or blood transfusions were reported in either group. The posterior approach to uterine artery ligation in the BUAL group was more time-efficient.ConclusionSecuring the uterine arteries at their origin during TLH reduces blood loss and provides a feasible alternative to conventional methods, despite a slightly longer operative time. Enhanced surgical expertise correlates with reduced operative duration and improved outcomes.